2018
DOI: 10.1007/s10637-018-0612-y
|View full text |Cite
|
Sign up to set email alerts
|

The drug lag and associated factors for orphan anticancer drugs in Japan compared to the United States

Abstract: The approval of orphan anticancer drugs in Japan has increased to meet high social demand. Drug lag, namely the approval lag of new drugs, is recognized as a social issue in Japan. We investigated the approval lag and its components, submission lag and review-time lag, between Japan and the United States (US) to reveal whether an approval lag still exists, and to identify potential factors that may contribute to reducing the approval lag. Anticancer drugs approved in Japan between April 2004 and November 2017 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…The criteria for orphan drug designation have evolved; however, the key criteria are for prevalence and the medical plausibility over alternative treatments as well as the unmet needs of the patients [ 30 , 31 ]. Several previous studies have evaluated the impact of whether drugs were was approved as an orphan drug in the US and the regulatory pathway, including priority review, accelerated approval, and breakthrough therapy [ 3 , 12 ]. Our findings show that the regulatory pathway in the US did not have a significant effect on drug lag.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The criteria for orphan drug designation have evolved; however, the key criteria are for prevalence and the medical plausibility over alternative treatments as well as the unmet needs of the patients [ 30 , 31 ]. Several previous studies have evaluated the impact of whether drugs were was approved as an orphan drug in the US and the regulatory pathway, including priority review, accelerated approval, and breakthrough therapy [ 3 , 12 ]. Our findings show that the regulatory pathway in the US did not have a significant effect on drug lag.…”
Section: Discussionmentioning
confidence: 99%
“…Preparing the regulatory pathway of the local new drug application (NDA) requires generating local specific data for the target indication and population to address the potential ethnic difference of the efficacy or safety of the drug [ 9 , 10 , 11 , 12 ]. Bridging clinical studies are required to extrapolate the foreign clinical data to local populations for local regulatory approval [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 Furthermore, although drug lag had previously been marked for anticancer drugs, it may occur for drugs for orphan diseases in the future. 42 , 43 Clearly, patient access to drugs for orphan diseases is a global issue. 44 Thus, in the future, when considering the direction of public knowledge‐based application in Japan, we consider it necessary to apply this method of application to orphan diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, drug lag has recently been eliminated in Japan [41], and it is assumed that public knowledge-based application has been useful in eliminating drug lag [6,7]. Furthermore, while drug lag had previously been marked for anti-cancer drugs, it may occur for drugs for orphan diseases in the future [42,43]. Clearly, patient access to drugs for orphan diseases is a global issue [44].…”
Section: Accepted Articlementioning
confidence: 99%
“…[8][9][10] However, it has been reported that the approval lag still exists in some therapeutic areas. [10][11][12][13] Shortening the development start lag is important for reducing a large approval lag. 14 In Japan, drug development may be pursued using bridging strategies if overseas (non-Japanese) MRCTs are under way.…”
mentioning
confidence: 99%